The role of learning styles in intelligent tutoring systems - Alves, Paulo (2009)
The Bologna Process changes the educational paradigm, to be focus on the student and in the learning outcomes. The majority of e-learning platforms are used as mere repositories of content, based on the classroom paradigm and don’t support the individualism of each student learning process. Through the integration of new pedagogical methodologies based on students learning styles, we present an approach to intelligent tutoring systems in order to improve the learning process. This article is focused on the importance of learning styles to create the student model in intelligent tutoring systems and what was the student’s feedback about the adaptation of the system to each learning experience.